The Successful Use of Nitroglycerin for Uterine Hyperstimulation with Fetal Heart Rate Abnormality Caused by a Controlled-Release Dinoprostone Vaginal Delivery System (PROPESS): A Case Report - Sho Takakura; Hiroaki Tanaka; Naosuke Enomoto; Shintaro Maki; Tomoaki Ikeda (Medicina, 2021)
The PROPESS, a controlled-release dinoprostone vaginal delivery system, is a pharmacological cervical ripening intervention and promotes cervical change causing uterine contraction. During insertion of the PROPESS, uterine hyperstimulation could occur and result in fetal heart rate (FHR) abnormality. We report a case of uterine hyperstimulation accompanied with FHR abnormality caused by the PROPESS in a pregnant woman. Postural change, oxygenation, fluid infusion, and the immediate PROPESS removal were ineffective to address the adverse event, so we administered nitroglycerin for acute uterine relaxation. The nitroglycerin resulted in uterine relaxation, and the FHR abnormality was resolved immediately, thereby preventing an emergency cesarean section. Therefore, nitroglycerin could be considered an effective option for uterine hyperstimulation accompanied with FHR abnormality caused by the PROPESS.